Mechanical properties of concrete containing crushed cockle shell as coarse aggregate replacement - Hou Lee, Sii (2013)
Various studies have been conducted on different agriculture waste products to determine the effectiveness of their use as replacement material in concrete. Effort toward preserving natural source and reduce environmental problem has initiate the studies on integrating cockle shelf as replacement material in concrete production. This thesis investigate the workability and compressive strength of cockle shell concrete containing different superplasticizer(sp), sand and aggregate content. Concrete mixes containing 0.6%, 0.8% and 1.0% of superplasticizer were cast and subjected to water curing for 7 and 28 days. In addition, cockle shell concrete with 700kg/rn 3 , 800 kg/m' and 900 kg/m' sand content were cast before subjected to water curing. Furthermore, cockle shell concrete with proportion 1:1.8:0.7, 1:1.4:1.1 and 1:1:1.5 were casted to investigate the effect of coarse and fine aggregate content on workability and compressive strength. Workability test and compressive strength test were carried in accordance to BS1881:PartlO2:1983 and BS1881:Partll6:1983 respectively. Results show that appropriate amount of superplasticizer content able to increase the workability and compressive strength of concrete. 0.6% of sp produced 44.8 1MPa strength for cockle shell concrete. Increasing of sand content had reduced the workability of concrete but increase the compressive strength of concrete. 900 kg/m 3 sand content gave lowest workability but highest compressive strength which was 43.67MPa for cockle shell concrete. Meanwhile, 1:1.8:0.7 concrete proportion illustrated that lower volume of coarse aggregate and higher sand content produced higher compressive strength and workability. This ratio had produced cockle shell concrete with strength 45.9MPa. A suitable mix proportion of the ingredients would be able to produce concrete with the better strength.